Development of Variants of High-Performance Self-Compacting Concrete with Improved Resistance to the Attack of Sulfates - Terzijski, Ivailo; Kocáb, Dalibor; Štěpánek, Petr; Strnad, Jiří; Girgle, František; Šimůnek, Petr (MDPI, 2021)
This paper presents experimental and analytical work of which the main objective was to support the introduction of a new technology for the production of sewer pipes. In this technology, the pipes produced consist of two differently produced parts. The direct part uses conventional vibro press compacted concrete. In the curved part, on the other hand, self-compacting concrete technology is used. The cooperating company, Prefa Brno a.s., defined possible negative effects on concrete of sewer pipes. The task of the research team and now the author’s team was to propose a procedure for the development of suitable self-compacting concrete variants and subsequently the design of a methodology to verify their durability in aqueous environments containing sulfates. To increase the efficiency of the development, the model mortar method was used in the experimental work. That is, instead of the original concrete, a model mortar derived from it was tested. The principle and procedure of derivation of model mortars are described in the paper. In total, eight variants of model mortars were tested, and at least three of them fulfilled the requirements. An optional but beneficial part of the carried out work was the derivation and practical application of the time-anchored-triangles-of-cracking graphical method developed during the research. This method is used to quickly compare the degree of attack of different silicate composites tested in a common bath inducing type III corrosion.

This paper presents experimental and analytical work of which the main objective was to support the introduction of a new technology for the production of sewer pipes. In this technology, the pipes produced consist of two differently produced parts. The direct part uses conventional vibro press compacted concrete. In the curved part, on the other hand, self-compacting concrete technology is used. The cooperating company, Prefa Brno a.s., defined possible negative effects on concrete of sewer pipes. The task of the research team and now the author’s team was to propose a procedure for the development of suitable self-compacting concrete variants and subsequently the design of a methodology to verify their durability in aqueous environments containing sulfates. To increase the efficiency of the development, the model mortar method was used in the experimental work. That is, instead of the original concrete, a model mortar derived from it was tested. The principle and procedure of derivation of model mortars are described in the paper. In total, eight variants of model mortars were tested, and at least three of them fulfilled the requirements. An optional but beneficial part of the carried out work was the derivation and practical application of the time-anchored-triangles-of-cracking graphical method developed during the research. This method is used to quickly compare the degree of attack of different silicate composites tested in a common bath inducing type III corrosion.
Development of Variants of High-Performance Self-Compacting Concrete with Improved Resistance to the Attack of Sulfates
Keywords: High-performance concrete; self-compacting concrete; durability; sulfates; ground blast furnace slag; metakaolin; multifunctional admixture; crystalizing admixture; parameter comparison; graphical evaluation technique; High-performance concrete; self-compacting concrete; durability; sulfates; ground blast furnace slag; metakaolin; multifunctional admixture; crystalizing admixture; parameter comparison; graphical evaluation technique